We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
147
2
avatar+814 

Given that f(3)=5 and \(f(3x)=f(x)+2\)  for all x, find \(f^{-1}(11)\).

 Aug 27, 2018
 #1
avatar
+1

The answer is 81

you can see every time we multiply x by 3, the y goes up by 2

so 11-5=6

6/2=3

3^1*3^3=3^4=81

 Aug 27, 2018
 #2
avatar
+2

(This question a little chanellge to me. Difinitely fun!)

The first anwser is right,but I think my anwser is more specific.

given f(3)=5 

f(9)=f(3)+2=5+2=7

f(27)=f(9)+2=7+2=9

f(81)=f(27)+2=9+2=11

\({f}^{-1}(11)={f}^{-1}(f(81))=81\)

.
 Aug 27, 2018

6 Online Users

avatar
avatar